A Clouded Leopard in the Middle of the Road New Thinking about Roads, People, and Wildlife - Jones, Darryl (Cornell University Press, 2022)
A Clouded Leopard in the Middle of the Road is an eye-opening introduction to the ecological impacts of roads. Drawing on over ten years of active engagement in the field of road ecology, Darryl Jones sheds light on the challenges roads pose to wildlife—and the solutions taken to address them. One of the most ubiquitous indicators of human activity, roads typically promise development and prosperity. Yet they carry with them the threat of disruption to both human and animal lives. Jones surveys the myriad, innovative ways stakeholders across the world have sought to reduce animal-vehicle collisions and minimize road crossing risks for wildlife, including efforts undertaken at the famed fauna overpasses of Banff National Park, the Singapore Eco-Link, "tunnels of love" in the Australian Alps, and others. Along the way, he acquaints readers with concepts and research in road ecology, describing the field's origins and future directions. Engaging and accessible, A Clouded Leopard in the Middle of the Road brings to the foreground an often-overlooked facet of humanity's footprint on earth
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Jul 2022)
Keywords: Ecology; General Science; Nature Guides & Natural History; NATURE / Ecology; Animals -- Effect of roads on; Animals-Effect of roads on; Habitat conservation; Roads -- Environmental aspects; Roads-Environmental aspects; Wildlife crossings